Autoimmune Pancreatitis. Issue 7 (October 2015) - Okazaki, Kazuichi; Uchida, Kazushige
<x xml:space="preserve">Abstract</x> Abstract Before the immunoglobulin G4 (IgG4) era, autoimmune pancreatitis was proposed as a single clinical entity of autoimmune disease. In the IgG4 era, the following 2 subtypes have been proposed: type 1 is the pancreatic manifestation of IgG4-related disease and type 2 presents with granulocytic epithelial lesions. The characteristic features of type 1 are increased serum IgG4, lymphoplasmacytic sclerosing pancreatitis (abundant infiltration of IgG4+ plasmacytes and lymphocytes, storiform fibrosis, and obliterative phlebitis), other organ involvements (eg, sclerosing cholangitis, sclerosing sialadenitis, retroperitoneal fibrosis), and responsiveness to steroid. Diagnosis of both types can be made using the International Consensus Diagnostic Criteria. Different from type 2, approximately half of type 1 shows a relapse within 1 year after remission. Despite consensus for the initial steroid treatment, steroid maintenance and treatment for relapses are controversial. In the long term, approximately 10% of type 1 may develop chronic pancreatitis or pancreatic stone formation. It is controversial whether autoimmune pancreatitis is a risk factor for malignancy. Although the pathogenic mechanism remains unclear, multiple factors such as genetic background and abnormal immunity may be involved. Future studies should be conducted to identify more specific and novel biomarkers for each subtype, alternative treatment options for relapse, and the precise pathogenic mechanism.